Bimbingan Teknis Aplikasi Bela Pengadaan bagi Usaha Mikro dan Kecil - Aprilia, Rachma; Adhitama, Satria; Kustiani, Nur Aisyah (Jurnal Abdimas Multidisiplin, 2023)
Purpose: This activity aims to increase the literacy and competency of MSEs to become government goods and service providers through electronic systems, especially the Procurement Defense Application. Research Methodology: The form of activity is outreach and onboarding assistance which is held offline for 25 selected MSEs in the South Tangerang area. Results: The results of this activity show an increase in MSEs' knowledge of government procurement of goods and services. Conclusions: Socialization activities related to the potential for procurement of goods and services can increase the understanding of UMK so that it is hoped that it will encourage UMK's interest in participating in government procurement. Limitations: There are still technical problems in onboarding assistance and some UMK products are not in accordance with the needs of government work units. Contribution: This activity supports efforts to accelerate the use of UMK products in the procurement of government goods and services as mandated by Presidential Decree No. 2 of 2022.